Filtration of pectin extract from grapefruit peel and viscosity of pectin solutions - Arslan, N; Togrul, H (Elsevier Sci Ltd, 1996)
The yield of pectin extracted (85 degrees C, pH=2.5, 90 min) by acidified water in a ratio of 25 parts per part of dry peel from dried grapefruit peel was 21.1% (DM basis). The pectin extract was vacuum filtered at different temperatures and under various pressure differences, and the average specific cake resistances were determined. The specific cake resistance was highly dependent on the filtration pressure. The cake compressibility coefficients at 15 degrees C, 25 degrees C and 35 degrees C were calculated as 0.387, 0.379 and 0.379, respectively. The filtration rare observed at 15 degrees C was higher than that at 25 degrees C due to flocculation at low temperature. The effects of temperature and concentration on the viscosity of pectin solutions were examined at sir different temperatures between 10 degrees C and 60 degrees C and four concentration levels between 0.3 g/100 ml and 1.4 g/100 ml. The activation energy for viscous flow was in the range 2.10-3.77 kcal mol(-1). Finally, the combined effect of temperature and concentration on the viscosity was expressed as eta = 8.52 x 10(-5) exp(-1.6162 C +1.807 exp(0.5493 C)/RT).
Keywords: Juices; Fruit